Perbandingan Tingkat Volatilitas Harga Karet Alam Indonesia Dan Thailand Di Pasar Dunia (Forum Agribisnis, 2026)
Indonesia and Thailand are major exporters of natural rubber in the global market. TSNR natural rubber (HS 400122) is the natural rubber product with the highest export value. The prices of Indonesian and Thai natural rubber fluctuate, which affects export supply and the income of natural rubber farmers. The purpose of this study is to compare natural rubber prices and analyze the volatility of Indonesian and Thai natural rubber prices in the world market. This study uses secondary data for the period from January 2007 to December 2023. The export destination countries in this study are the United States, Japan, China, India, and South Korea. The analysis methods used in this study are quantitative, descriptive, and Autoregressive Conditional Heteroscedasticity and Generalized Autoregressive Conditional Heteroscedasticity (ARCH-GARCH). The results of the study show that the prices of Indonesian and Thai natural rubber are unstable, and the volatility of Indonesian and Thai natural rubber prices is low in the world market. The policy implications are bilateral trade cooperation between Indonesia and Thailand in natural rubber, increasing the competitiveness of natural rubber exports and consumption (downstreaming), strengthening natural rubber diplomacy in the ITRC organization, natural rubber production investment strategies in the ASEAN region, and increasing the capacity of farmers.